The Use of Youtube Media as Media to Improve Writing Skills on Greeting Card to Eighth Grade Student of SMP Negeri 6 Tabanan - Suamba Made; Ni Putu Wulantari (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This research is aimed at improving students’ writing skills on greeting card by using YouTube media. The subject of this research was the eighth-grade students of SMP N 6 Tabanan in the academic year 2022/2023 consisting of 32 students. This research was conducted by using the Classroom Action Research conducted in two cycles involved Cycle I and Cycle II. Each cycle consisted of planning, action, observation and reflection. The data were collected by using observation, documentation and test. The data were analysed by using qualitative and quantitative data analysis. The procedure of this research was used pre-test and post-test. The result indicated that the mean scores of students on the writing skills in the pre-test was 57.18 and the percentage of students passed the minimum completeness criteria was 21.87%. In the post-test I, the mean scores of students was 67.81 and the percentage of students passed the minimum completeness criteria was 53.12%. The mean score of students was 76.25 and the percentage of students passed the minimum completeness criteria was 78.12% in post-test II. Based on the result above, the use YouTube media is able to enhance students writing skill on greeting card. The use of YouTube media are also able to students stimulate motivation and enthusiasm in English class, especially in writing.